Assessing Nighttime Deliveries in Stockholm, Sweden. Issue 1 (January 2017) - Koutoulas, Anastasios; Franklin, Joel P.; Eliasson, Jonas
Off-peak-hour delivery programs are a promising but challenging concept for promoting sustainable urban logistics. Stockholm, Sweden, initialized a nighttime freight deliveries program in 2014, aimed at a more efficient and environmentally friendly delivery system within the central area of the city. The policy of shifting freight deliveries from daytime to off-peak hours generates a wide range of effects that can be analyzed from several angles. This paper identifies the social costs and benefits, how these are distributed between stakeholders, and their effects on the everyday life and operations of all interested parties. According to information and data collected through in-depth interviews with private and public stakeholders, the social benefits mainly consist of increased efficiency and productivity for carriers and receivers, reduced transport costs, fuel cost savings, and reduced congestion and accidents when trucks are moved from peak to off-peak hours. Social costs may include increased noise levels and noise disturbances; additional staff requirements, equipment, and wage costs; and higher risks in handling goods deliveries at nighttime, especially in the case of unassisted deliveries. This paper concludes by discussing the lessons learned from the trial, challenges and opportunities that arose during implementation, and the implications for enhancement of off-peak-hour delivery in Stockholm and other cities.